Simple Fabrication of Structured Magnetic Metallic Nano-Platelets for Bio-Analytical Applications - Novotny, Jakub; Juskova, Petra; Kupcik, Rudolf; Bilkova, Zuzana; Foret, Frantisek (Micromachines, 2019)
This short communication presents a simple method of preparation of thin-metal nano-platelets utilizing metal sputtering and lift-off photolithography. The method offers complete control over size, shape and properties of nano-platelets of sub-micrometer thickness. Platelets with a thickness of 50⁻200 nm and with defined arbitrary shapes and sizes in the range of 15⁻300 μm were prepared from single or multiple metal layers by magnetron sputtering. Deposition of different metals in layers enabled fabrication of bi- or tri-metallic platelets with a magnetic core and differently composed surfaces. Highly reflective nano-platelets with a magnetic core allowed manipulation by magnetic fields, while different metallic surfaces served for functionalization by selected molecules. Submicron thin nano-platelets are extremely light (e.g., ~20 ng for a 100 μm × 100 μm × 0.1 μm gold nano-platelet) so that they can be attached to surfaces by only a few chemical bonds. At the same time their area is sufficiently large for simple optical recognition of their shape which is intended to label various characteristics depending on the specific surface functionalization of the given shape.
Keywords: magnetic particles; lithography; micro-particles